Antiangiogenic 1‐Aryl‐3‐[3‐(thieno[3, 2‐b]pyridin‐7‐ylthio)phenyl]ureas Inhibit MCF‐7 and MDA‐MB‐231 Human Breast Cancer Cell Lines Through PI3K/Akt and MAPK/Erk Pathways. Issue 12 (15th June 2016) - Machado, Vera A.; Peixoto, Daniela; Queiroz, Maria João; Soares, Raquel
ABSTRACT: Breast cancer is the most frequently diagnosed cancer and the second leading cause of cancer related deaths among women worldwide. The purpose of this study is to evaluate the cytotoxic effects and possible molecular mechanisms of the antiproliferative properties of the antiangiogenic 1‐aryl‐3‐[3‐(thieno[3, 2‐ b ]pyridin‐7‐ylthio)phenyl]ureas1a–e, prepared earlier by us, on two human breast cancer cell lines of distinct histological types: hormone‐dependent MCF‐7 (ER positive), and hormone independent MDA‐MB‐231 (ER/PR/HER2 negative), this latter being the most aggressive and difficult to treat. Our findings clearly demonstrated that compounds1a –e suppress breast cancer cell survival, proliferation, migration, and colony formation at very low concentrations, not showing cytotoxicity in normal human mammary cells (MCF‐10A). TUNEL assay demonstrated that compounds1a –e induced apoptosis in MDA‐MB‐231, but not in MCF‐7 at the concentrations tested. PI3K/Akt and MAPK/Erk cell signaling pathways were investigated using Western blot analysis, revealing that these compounds decrease their activity in both breast cancer cell lines. Compounds1b (R 2  = F), 1c (R 2  = Me), and1e (R 1  = Cl, R 2  = CF3 ) were the most effective particularly in MDA‐MB‐231 cells. Overall, 1c and1e compounds are the most promising antitumor compounds. These findings, together with the antiangiogenic activity previously described by us, render these compounds a relevant breakthrough for cancer therapy. J. Cell. Biochem. 117: 2791–2799, 2016. © 2016 Wiley Periodicals, Inc. Abstract : This study investigated the effect of synthesized compounds, which are known to bind tyrosine kinase receptors overexpressed in tumor cells, in two human breast cancer cell lines: MCF7 and MDA‐MB‐231. We found out that some of these compounds were able to inhibit cell growth, migration, colony formation, and downregulate Akt and Erk molecular downstream effectors of cell receptors in these cell lines. Normal MCF10A epitelial cells viability was not affected by these compounds. Effects in the triple negative (MDA‐MB‐231) cells were higher. These compounds are potential therapeutic agents against triple negative breast cancer.